Face-to-face dialogue : theory, research, and applications - Bavelas, Janet Beavin 1940-2022 (Foundations of human interaction (Oxford University Press), 2022)
Janet Beavin Bavelas proposes that face-to-face dialogue is the primary site of language use, with unique features that make it the fastest, most precise, and most skillful activity that ordinary individuals do together. Writing for an inter-disciplinary readership, Bavelas draws on decades of experimental research combined with qualitative measures to illustrate the advantages of focusing on dialogue (rather than on individuals) and of using a multi-modal lens.